The Application of Fat-Free Mass Index for Survival Prediction in Cancer Patients With Normal and High Body Mass Index - Zhang, Xi; Zhang, Qi; Feng, Li-jin; Zhang, Kang-Ping; Tang, Meng; Song, Meng-meng; Ruan, Guo-tian; Zhang, Xiao-wei; Li, Wei; Zhou, Fu-xiang; Cong, Ming-Hua; Shi, Han-Ping (Frontiers in Nutrition, 2021)
Background: Fat-free mass (FFM) depletion can be masked by a stable body weight or weight gain in the presence of a normal or high body mass index (BMI). This study investigated the prognostic value of low fat-free mass index (FFMI) in cancer patients with normal or high BMI. Methods: This multicenter retrospective cohort study included 1602 cancer patients with normal/high BMI. The association of FFMI with patients’ overall survival (OS) was analyzed by the Kaplan-Meier method and a Cox model. Results: In this analysis, there were 974 (60.8%) females and 628 (39.2%) males. Low FFMI was associated with worse OS when compared with those patients with normal FFMI. After multivariate adjustment, low FFMI was demonstrated to be an independent unfavourable prognostic factor (HR: 1.69; 95% CI: 1.28, 2.23; P<0.001) in cancer patients with normal/high BMI. For specific tumor type, low FFMI was found to be associated with worse prognosis in patients with lung cancer, breast cancer and upper gastrointestinal cancer. In subgroup analysis, the association of low FFMI with worse survival was significantly modified by weight loss (P for interaction=0.012), and those patients with concurrent low FFMI and weight loss showed the worst prognosis (HR: 3.53; 95% CI: 2.04, 6.11; P<0.001). Conclusions: Low FFMI was associated with worse prognosis in cancer patients with normal/high BMI. This study highlights the usefulness of FFMI for prognostic estimation in these patients.